Explosion Prevention in the Present Conditions of Production - Libor Stroch (Communications - Scientific letters of the University of Zilina, 2008)
The article solves some questions of possible approaches to explosion prevention in production plants. In the introductory part it deals with thoughts about the safety of personnel in an industrial plant in areas with an explosion danger. Further, it defines individual views of industrial plants and suggests the means of solving the explosion prevention in industry. In the conclusion it recommends an approach to the described questions and the means of ensuring asystematic development in the field of explosion prevention.